Effects of millionaire’s mind programming on entrepreneurial performance through entrepreneurial motivation - Abdullah, Moha Asri; Kedah, Zulkarnain; Anwar, Md. Aftab (2016)
The spotlight of this study is to examine the attributes and essential elements of millionaire’s mind programming and to utilize a contemporary psychological method to evaluate consciousness that enhance entrepreneurial performance through entrepreneurial motivation among the entrepreneurs in Malaysia. The premise of this point of convergence is to know which elements of an entrepreneurial mind programming are deficient and to have the capacity to concoct thoughts that can be utilized to enhance these lacking for entrepreneurial success. The study represents a significant positive relationship between millionaire’s mind programming and entrepreneurial performance mediated by entrepreneurial motivation. The findings of the results also confirm that millionaire’s mind programming is an important factor among other factors that have influenced over entrepreneurial motivation. The outcome of the study will help the training and development authorities to take necessary steps to outline a new and productive content for potential entrepreneurial development.